Do natural disasters have long-term effects on growth? (2009)
Large natural disasters (LNDs) are ubiquitous phenomena with potentially large impacts on the infrastructure and population of countries and on their economic activity in general. Using a panel of 113 countries and 36 years of data, I examine the relationship between different measures of natural disaster impact and long-run economic growth. The sample is partitioned in two separate ways: according to the amount and type of disasters that countries have experienced and to the size of those disasters. For each partition, I present two sets of econometric estimations. The first regressions identify short-run and longer-lasting effects of LNDs. However, these first estimations do not distinguish between temporary but persistent effects and truly permanent ones. I thus estimate a structural model that allows me to identify permanent changes. The results of the first regressions show that for some of the groups of countries the disaster impact persists beyond the 2-5 years in which reconstruction and adaptation are expected to have an effect on the economy. However, the estimates using the structural model show that only for a very small number of countries which share a history of highly devastating natural disasters the negative effects are truly permanent.